Faktor Pengaruh Berkunjung Kembali Pada Pariwisata Di Kota Kudus dan Kepuasan Pengunjung Sebagai Variabel Intervening - Nisa, Yasinta Khoirun; Andni, Riyan (Jurnal Ilmiah Ekonomi Islam, 2024)
Kudus City is one of the cities with numerous tourist destinations, particularly in halal tourism. The influx of visitors necessitates the development of facilities that align with their preferences to ensure satisfaction and encourage repeat visits. This study aims to assess the impact of halal facilities and social media on the interest in revisiting, with visitor satisfaction serving as an intervening variable. This quantitative research employs the Path Analysis method, supported by IBM SPSS software version 27. The findings reveal that the variables of halal facilities and social media positively and significantly affect visitor satisfaction, thus confirming the hypothesis. Furthermore, these variables also positively and significantly influence the interest in revisiting, which again supports the hypothesis. The study also finds that halal facilities and social media have a positive and significant impact on the interest in returning through the mediating variable of visitor satisfaction, validating the hypothesis. Additionally, the social media variable has a positive and significant effect on the interest in revisiting, reinforcing the hypothesis. However, the influence of the halal facility variable on the interest in revisiting is found to be insignificant, leading to the rejection of this particular hypothesis.